A review of bobbin friction stir welding process with post-weld cooling assisted approach - Sued, Mohammad Kamil; Tham, Sook Chan; Sahaya Anand, Joseph (Semarak Ilmu Publishing, 2025)
Over the last two decades, friction stir welding (FSW) has emerged as one of the most promising technologies, especially when dealing with difficult-to-weld materials. FSW is frequently employed in the heat-treatable aluminium series and is applicable to alloys that are susceptible to heat damage during welding, which is a result of the advancement of solid-state technology. FSW is not a flawless process, and its limitations should be recognized. The constraints of this process must be identified and understood for better process improvement. Studies further concluded that bobbin friction stir welding (BFSW) minimizes these limitations. The bobbin weld usually begins with a slowly applied force on the edge of the base plate, moving at low speed until plasticdeformation is realized. The welding speed then continues to advance with the introduction of higher speeds until an entire weld is formed. All the same, the BFSW welded joint strength is realized to be much below that of FSW. This is essentially attributed to the bobbin tool having a double shoulder, which generates a tremendous amount of heat. There is a restriction in the aspect of optimization, whereby it can be done just through the control of the process parameters. Therefore, this review paper endeavours to explain the role that cooling aids play in terms of joint strength, that is, the mechanical properties. The information gained from the summarization of technical information in this paper carries valuable insight into the approach of cooling-assisted BFSW and its respective parameters. Attention was focused on the basic ideas that go along with it, such as how heat is generated during welding and how process parameters affect mechanical properties, especially joint strength, which includes tensile strength and hardness. An increase in strength performance was exhibited where ordinary BFSW was inferior to the cooling-assisted BFSW, which was said to increase the joint tensile strength by 10%. This article is helpful to academics, researchers, and professionals in that it points out relevant features of the cooling-assisted BFSW process while identifying the future research that is required to be conducted.